Development of collaborative flipped instruction for form one Malay language writing / Nurul Hijja Mazlan - Nurul Hijja , Mazlan (2020)
The aim of this study is to develop a Collaborative Flipped Instruction for Form One Malay Language Writing through Design and Development Research. Declared a national language in Malaysia, Malay language is a compulsory subject in the national education system. Although many students in Malaysia have passed their Malay language papers on national examinations, their language skills, including writing, are evidences of conflict. Backlog issues related to Malay language writing are not limited to the writing skills themselves, but are also demonstrated by the low rate of technology integration in its writing instruction. Comprised of three phases – Needs Analysis, Design and Development, and Implementation and Evaluation, multiple methods have been used in each phase to achieve the objectives. During the Needs Analysis phase, Malay language teachers in Kuala Lumpur were interviewed, surveys were conducted among eighty-seven Form One students from national secondary school in Kuala Lumpur, and document analysis of writing artifacts and statistical documents was conducted. These triangulation methods have been used to analyze the needs in the Collaborative Flipped Instruction for Form One Malay Language Writing. The analysis of needs involved content, technology and infrastructure, as well as situational factors-focused on user needs and localized background issues. The aim is to inform the next design process. The Design and Development phase is the next step, using rigorous methods – an interview with four experts and a consolidated consensus of eighteen experts through the Fuzzy Delphi method. The development of the module was then proceeded based on the result of the design phase. The final phase is the Implementation and Evaluation in which the usability of the module was investigated through interviews with seven Form One students and their Malay language teacher at the national secondary school in Kuala Lumpur. They were involved in the implementation of the flipped instruction. Results from the Needs Analysis phase have shown that tacit knowledge of the writing process is the main issue lingered around teachers, negatively affecting the development of writing skills among students. Besides that, individual factors coupled with pedagogy issues also contributed to the problems. The study also investigates the pattern of technology usage among students and teachers. There is, therefore, a need for research-based writing instruction, taking into account students' inclination towards social media technology. Meanwhile, the findings of the Design and Development phase identified the components and sub-components of the Collaborative Flipped Instruction for Form One Malay Language Writing based on expert consensus. Next, the findings of the Implementation and Evaluation phase investigated the flaws and strength of the module, as well as the suggestions for improvement from the users’ retrospective. Implications and recommendations for future researchers and practitioners were then presented.